New generation of camptothecin derivatives spontaneously alkylating DNA. (5th August 2016) - Naumczuk, Beata; Wiktorska, Katarzyna; Lubelska, Katarzyna; Kawęcki, Robert; Bocian, Wojciech; Bednarek, Elżbieta; Sitkowski, Jerzy; Chilmonczyk, Zdzisław; Kozerski, Lech
Abstract : The IC50 values of new derivatives2(a–e) for blood and lung cancer cells are comparable to SN38, and a few orders of magnitude higher than for irinotecan. Abstract : 9-Aminomethyl derivatives of 7-ethyl-10-hydroxycamptothecin were synthesized. Interaction with a natural DNA octamer was checked using 1 H NMR, PFGSE NMR and MALDI-TOF experiments, which proved covalent binding. Compounds were tested against human cancer cell lines in vitro. All compounds show high activity comparable to SN38. The obtained products are well soluble in water.